Estimating the economic costs of skin cancer in New South Wales, Australia - Doran, Christopher M. (BMC Public Health, 2015)
BACKGROUND: Skin cancer is one of the most common cancers in the world. The increased incidence of skin cancer, combined with limited health care resources and tight budgetary conditions, has increased the importance of understanding the economic impact of skin cancer. This research estimates the economic cost of skin cancer in the Australian state of New South Wales. METHOD: An incidence based approach is used to estimate lifetime costs of skin cancer. Both direct and indirect costs are considered - direct costs include resources associated with the management of skin cancer and indirect costs refer to productivity costs associated with morbidity and premature mortality. Diagnosis of skin cancer was determined according to ICD-10 codes using principal diagnosis. Linked administrative data and regression modelling are used to calculate costs; presented as Australian dollars for the year 2010. The human capital approach is used to value present and future productivity losses. RESULTS: The lifetime cost of the 150,000 incident cases of skin cancer diagnosed in NSW in 2010 is estimated at $536 million ($44,796 per melanoma and $2459 per non-melanoma). Direct costs accounted for 72 % of costs ($10,230 per melanoma and $2336 per non-melanoma) and indirect costs accounted for 28 % of costs ($34,567 per melanoma and $123 per non-melanoma). Direct costs are, on average, higher for females than males with indirect costs, on average, higher for males than females. CONCLUSION: This research provides new evidence on the economic cost of skin cancer and provides policy makers with information of the potential monetary savings that may arise from efforts to reduce the incidence of skin cancer.